Simulation-Based Design and Optimization of Rectangular Micro-Cantilever-Based Aerosols Mass Sensor - Feng Xu; Yuliang Wei; Shiyuan Bian; Huanqin Wang; Da-Ren Chen; Deyi Kong (Sensors, 2020)
Micro-Cantilever (MCL) is a thin film structure that is applied for aerosol particle mass sensing. Several modifications to the rectangular MCL (length-to-width ratio, slots at the anchor, serrations at its side edges) are made to deduce the role and influence of the shape of rectangular MCL-based aerosol mass sensors and reduce gas damping. A finite element fluid-structure interaction model was used to investigate the performance of MCL. It is found that (I) the mass sensitivity and quality factor decline with the increasing of length-to-width ratio which alters the resonant frequency of the MCL. The optimum conditions, including the length-to-width ratio (σlw = 5) and resonant frequency (f0 = 540.7 kHz) of the MCL, are obtained with the constant surface area (S = 45,000 μm2) in the frequency domain ranging from 0 to 600 kHz. (II) The slots can enhance the read-out signal and bring a small Q factor drop. (III) The edge serrations on MCL significantly reduce the gas damping. The results provide a reference for the design of aerosol mass sensor, which makes it possible to develop aerosol mass sensor with high frequency, sensitivity, and quality.